Periclimenaeus nielbrucei sp. nov. (Crustacea: Decapoda: Pontoniinae), a new sponge associate from the Capricorn Islands, Queensland, with notes on related Periclimenaeus species - Bruce, A. J. (Zootaxa, 2006)
Periclimenaeus nielbrucei sp. nov., a coral reef sponge associate, is described from specimens from the Capricorn Islands, Great Barrier Reef, Queensland, Australia. The rostral dentition is unique in Periclimenaeus, with the dorsal carinal teeth diverging irregularly from the midline. The Australian Periclimenaeus fauna is now increased to 24 species.